Targeting mutant p53: Evaluation of novel anti-p53R175H monoclonal antibodies as diagnostic tools - Diana Spiegelberg; Le-Ann Hwang; Khian Hong Pua; Sashwini Chandra Kumar; Xin Yu Koh; Xiao Hui Koh; Ram Kumar Selvaraju; Kanaga Sabapathy; Marika Nestor; David Lane (Scientific Reports)
Abstract About 50% of all cancers carry a mutation in p53 that impairs its tumor suppressor function. The p53 missense mutation p53R175H (p53R172H in mice) is a hotspot mutation in various cancer types. Therefore, monoclonal antibodies selectively targeting clinically relevant mutations like p53R175H could prove immensely value. We aimed to evaluate the in vitro and in vivo binding properties of two novel anti-p53R175H monoclonal antibodies and to assess their performance as agents for molecular imaging. In vitro, 125I-4H5 and 125I-7B9 demonstrated long shelf life and antigen-specific binding. Our in vivo study design allowed head-to-head comparison of the antibodies in a double tumor model using repeated SPECT/CT imaging, followed by biodistribution and autoradiography. Both tracers performed similarly, with marginally faster blood clearance for 125I-7B9. Repeated molecular imaging demonstrated suitable imaging characteristics for both antibodies, with the best contrast images occurring at 48 h post-injection. Significantly higher uptake was detected in the mut-p53-expressing tumors, confirmed by ex vivo autoradiography. We conclude that molecular imaging with an anti-p53R175H tracer could be a promising approach for cancer diagnostics and could be further applied for patient stratification and treatment response monitoring of mutant p53-targeted therapeutics.